Exercise Therapy for Management of Type 2 Diabetes Mellitus: Superior Efficacy of Activity Monitors over Pedometers - Masaaki Miyauchi; Masao Toyoda; Noriko Kaneyama; Han Miyatake; Eitaro Tanaka; Moritsugu Kimura; Tomoya Umezono; Masafumi Fukagawa (Journal of Diabetes Research)
We compared the efficacy of activity monitor (which displays exercise intensity and number of steps) versus that of pedometer in exercise therapy for patients with type 2 diabetes. The study subjects were divided into the activity monitor group (n=92) and pedometer group (n=95). The primary goal was improvement in hemoglobin A1c (HbA1c). The exercise target was set at 8,000 steps/day and 20 minutes of moderate-intensity exercise (≥3.5 metabolic equivalents). The activity monitor is equipped with a triple-axis accelerometer sensor capable of measuring medium-intensity walking duration, number of steps, walking distance, calorie consumption, and total calorie consumption. The pedometer counts the number of steps. Blood samples for laboratory tests were obtained during the visits. The first examination was conducted at the start of the study and repeated at 2 and 6 months. A significant difference in the decrease in HbA1c level was observed between the two groups at 2 months. The results suggest that the use of activity level monitor that displays information on exercise intensity, in addition to the number of steps, is useful in exercise therapy as it enhances the concept of exercise therapy and promotes lowering of HbA1c in diabetic patients.